Synthesis of Polyester Nanofiltration Membrane for Removal of Natural Organic Matter - Nurasyikin, Jusoh (2012)
Natural Organic Matter (NOM) in surface water usually refers to humic and fulvic acids that are decayed by-products of plants such as those found in surface waters shallow well aquifers. Performance on humic acid removal from natural organic matter using Nanofiltration (NF) has been investigated in this study. Since most of the organic matter in groundwaterhas smaller between 200-500 D of the pore sizes, the useof the NF process was proposed. Thin-film composite nanofiltration membranes were prepared via interfacial polymerization of triethanolamine and trimesoyl chloride with different concentration and reaction time. The separation process was conducted by separating solution that contains humic acid to get the best result based on varying the concentration and reaction time for interfacial polymerization. In term of concentration of monomers has shown that 4% TEOA has gives more rejection of humic acid. As for reaction time, meanwhile10 minutes of TMC reaction time shows higher performance in removing humic acid. Fouling is still occur because of the tendency of humic acids appears to be dueto their ability to bind to multivalent salts.